Penilaian Modul Aplikasi Adobe Illustrator Komputer Desain Materi Rok dan Celana - Rania Fitri Rabbani; Noerharyono, Muchammad; Wesnina, Wesnina (Practice of Fashion and Textile Education Journal, 2024)
Abstract. This study aims to determine the results of the Assessment Module of the Application Adobe Illustrator Computer Design Material Design Skirts and Pants based on characteristics of module and quality elements of module. The method used is Pre-Experiment with One Shot Case Study design as measured by rating scale. The data analysis technique used is Descriptive Quantitative. The data collection technique used closed-open (mixed) questionnaire using characteristics of module which includes Self Instruction, Self Contained, Stand Alone, Adaptive, User Friendly, and also using quality elements of module which includes format, organization, attractiveness, shape and size of letters, space (blank space), as well as consistency. The results of research based on characteristics of module by 2 expert panelists got a percentage of 95.71% with the highest score obtained for User Friendly aspect which was 100% while the lowest score was obtained for Self Contained aspect with a value of 93.75%. Assessment based on module quality elements by 2 expert panelists got a percentage of 93.97% with the highest score obtained for Shape and Size aspect of Letters which was 100% while the lowest score was obtained for Organizational aspect with a value of 91%. Then overall it gets a percentage of 94.92% so that module is in the Very Good category.